Desempenho e uso eficiente da terra de modalidades de con-sorciação com milho e forrageiras - Ferreira, Eduardo André; Coletti, Admar Junior [UNESP]; da Silva, Wininton Mendes; de Macedo, Fernando Giovannetti; de Albuquerque, Amanda Nogueira (My University, 2014)
This study was developed with the aim of evaluating the performance and land use efficiency of different arrangements of intercropping with maize and forage. The field experiment was conducted in Tangará da Serra/MT. The experimental design was a randomized block in factorial scheme 3x2 +1, were as three arrangements of intercropping, two species of forage and an additional treatment with maize monoculture in four replication. In maize monoculture and intercropping were evaluated: plant height and ear insertion height, plant population, weight of 100 grains, productivity, number of grain rows and number of grain per row. In forages intercropping with maize were evaluated plant population and dry matter accumulation. The arrangements with Maize + Forage sown in the line and Maize + Forage sown in two rows between rows with the species Urochloa hybrid promoted best corn yields. The modality and species affect both the productivity of maize as forages species. Grain yield of maize is higher in monoculture. The higher dry matter accumulation of Urochloa hybrid occurs in the Maize + Forage sown in one row between rows, while, for the Urochloa brizan-tha the arrangements studied do not affect their yields. The arrangement with best land use efficiency is Maize + Forage sown in two rows between rows for both study forage species.
Performance and land use efficient of arrangements with corn and forage intercropping
Keywords: Competition; Crop-livestock integration; Grain production; Intercropping Tillage; Urochloa